2019
DOI: 10.3390/app9061247
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation Characteristics of Lactobacillus Plantarum and Pediococcus Species Isolated from Sweet Sorghum Silage and Their Application as Silage Inoculants

Abstract: This study aims to evaluate the fermentation characteristics of Lactobacillus plantarum and Pediococcus spp isolated from sweet sorghum silage to enhance the fermentation quality of Napier grass and sweet sorghum silage. Based on molecular 16S ribosomal ribonucleic identification the isolated strains were phylogenetically related to Lactobacillus plantarum (HY1), Pediococcus acidilactici (HY2) and Pediococcus claussenii (HY3). Strains HY1, HY2 and HY3 and commercial bacteria Lactobacillus plantarum, Ecosyl; (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 45 publications
(52 reference statements)
3
32
1
Order By: Relevance
“…The homofermentative inoculants produced a sufficient amount of lactic acid, and the LAB-treated silages in this study all had lower pH values than the control. Filya et al [ 28 ] and Alhaag et al [ 29 ] also reported that the application of Lactobacillus plantarum to sorghum silage significantly improved the lactic acid contents and reduced the acetic acid and propionic acid contents. The efficiency of the fermentation was promoted by the LAB treatments at 20 and 30 °C.…”
Section: Discussionmentioning
confidence: 99%
“…The homofermentative inoculants produced a sufficient amount of lactic acid, and the LAB-treated silages in this study all had lower pH values than the control. Filya et al [ 28 ] and Alhaag et al [ 29 ] also reported that the application of Lactobacillus plantarum to sorghum silage significantly improved the lactic acid contents and reduced the acetic acid and propionic acid contents. The efficiency of the fermentation was promoted by the LAB treatments at 20 and 30 °C.…”
Section: Discussionmentioning
confidence: 99%
“…Despite all strains were suitable for sorghum ensiling, significant amounts of viable LAB were found after 30 days of fermentation only when LpM15 was used. In a recent work ( Alhaag et al, 2019 ), two L. plantarum strains were employed for sorghum silages (a commercial one and another isolated from sorghum) and, although both strains preserved the silages overall quality, the commercial strain was not found viable after 30 days of ensiling. Viable LAB in silages may display a potential probiotic role for ruminants (Acosta Aragon, 2012 ; Ellis et al, 2016 ; Fabiszewska et al, 2019 ), an hypothesis that needs further studies, then viability along storage may be considered a potential advantage.…”
Section: Discussionmentioning
confidence: 99%
“…LAB population in forage samples are very less, it's not sufficient to initiate the fermentation rapidly and also unable to produce a higher concentration of lactic acid during fermentation, this condition could favor the growth of clostridia and causes deterioration of silage quality [38]. Many reports claimed that an addition of L. plantarum, L. pentosus, and Pediococcus pentosaceus effectively ferment the different types of grass and legume plants and preserve its life for a long time [39][40][41]. Therefore, the addition of LAB is essential criterion for enhancing the fermentation process and rapidly decreased the pH of the silage by producing a higher amount of lactic acid with a lesser extent to acetic acid.…”
Section: Discussionmentioning
confidence: 99%